An efficient isolation method for polyadenylated messenger ribonucleic acid from Neurospora mycelia - K. Furukawa; K. Hasunuma; Y. Hamada (Fungal Genetics Reports, 1987)
An efficient isolation method for polyadenylated messenger ribonucleic acid from N. crassa.